Association Between Excessive Alcohol Consumption and Echocardiographic Parameters According to the Presence of Flushing Reaction in Korean Men: A Community‐Based Study. (14th April 2018) - Ko, Hyeonyoung; Song, Yun‐Mi; Lee, Sang‐Chol; Park, Seung Woo; Sung, Joohon; Lee, Kayoung; Lee, Eunae
Abstract : Background: The objective of this study was to investigate the effect of excessive alcohol consumption on heart reflected by various echocardiographic parameters according to the presence or absence of flushing reaction that might reflect acetaldehyde metabolism. Methods: A total of 854 Korean men without significant cardiovascular diseases who underwent echocardiography and participated in the Korean Healthy Twin Study were used as subjects of this study. These subjects were classified into 3 categories: nondrinker, moderate drinker (≤196 g/wk), and heavy drinker (>196 g/wk) within 2 strata of flushing reaction to alcohol drinking. Association between echocardiographic measurements and categories of the amount of alcohol consumption considering flushing reaction were evaluated using mixed linear regression model. Results: The proportion of flushers among drinkers was 39.5% (278 of 703). In stratified analysis by flushing reaction, nonflushers showed significantly higher left ventricular mass index ( β : 4.605; 95% CI: 0.966, 8.243) and significantly lower ratio of peak early diastolic velocities ( E peak) over peak late diastolic velocities of mitral inflow ( β : −0.103; 95% CI: −0.198, −0.008) in heavy drinkers compared to nondrinkers. Flushers showed significantly higher left atrial (LA) volume index ( β : 2.712; 95% CI: 0.456, 4.968) in heavy drinkers and significantly lower ratio of E peak over the peak early diastolic mitral annular velocities ( β : −0.493; 95% CI: −0.902, −0.085) in moderate drinkers compared to nondrinkers. However, the interaction according to flushing reaction was only statistically significant for the association between alcohol consumption and LA volume index ( p for interaction = 0.004). Conclusions: Alcohol consumption is associated with changes in cardiac structure and function. Such association might be influenced by acetaldehyde metabolism.